2012
DOI: 10.1002/adsc.201200684
|View full text |Cite
|
Sign up to set email alerts
|

Cyanide as a Powerful Catalyst for Facile Preparation of 2‐Substituted Benzoxazoles via Aerobic Oxidation

Abstract: A cyanide-catalyzed synthesis of 2-substituted benzoxazoles from Schiff bases via aerobic oxidation has been developed. The products from various Schiff bases were obtained in high yields in an open flask under ambient conditions without other external oxidants. We have also developed a simple one-step protocol for the synthesis of benz-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…The TPT‐DAHQ COF was synthesized in a Pyrex tube through one‐pot solvothermal condensation between TPT‐3CHO (Figures S1–S4) and DAHQ‐2HCl in N , N ‐dimethylformamide (DMF), over 72 h at 120 °C. As reported previously, the formation of the benzoxazole ring presumably occurred in a three‐step sequence (Scheme S1): (i) formation of a phenolic Schiff base intermediate, (ii) nucleophilic addition of the cyanide nucleophile to the imino (C=N) bond to accelerate ring cyclization and the formation of a benzoxazoline intermediate, and (iii) formation of the benzoxazole ring upon aerobic oxidation of the benzoxazoline intermediate …”
Section: Figurementioning
confidence: 56%
See 1 more Smart Citation
“…The TPT‐DAHQ COF was synthesized in a Pyrex tube through one‐pot solvothermal condensation between TPT‐3CHO (Figures S1–S4) and DAHQ‐2HCl in N , N ‐dimethylformamide (DMF), over 72 h at 120 °C. As reported previously, the formation of the benzoxazole ring presumably occurred in a three‐step sequence (Scheme S1): (i) formation of a phenolic Schiff base intermediate, (ii) nucleophilic addition of the cyanide nucleophile to the imino (C=N) bond to accelerate ring cyclization and the formation of a benzoxazoline intermediate, and (iii) formation of the benzoxazole ring upon aerobic oxidation of the benzoxazoline intermediate …”
Section: Figurementioning
confidence: 56%
“…As reported previously,the formation of the benzoxazole ring presumably occurred in at hree-step sequence (Scheme S1): (i)formationo faphenolic Schiff base intermediate, (ii)nucleophilic addition of the cyanide nucleophile to the imino( C =N) bond to accelerate ring cyclization andt he formation of ab enzoxazoline intermediate, and (iii)formation of the benzoxazole ring upon aerobic oxidation of the benzoxazoline intermediate. [19] The formation of benzoxazole rings and the synthesis of TPT-DAHQ COF were confirmed using Fouriert ransform infrared (FTIR) spectroscopy,s olid state 13 Cc ross-polarization( CP)/ magic angle spinning (MAS) NMR spectrum, and elemental analysis. The FTIR spectrumo fD AHQ-2HCl ( Figure S5) was characterized by ab road signaln ear 3200 cm À1 ,a ttributed to the phenolic (OH) and ammonium (NH 3 Cl) units, in addition to other peaks at 1555 cm À1 for the aromatic (C=C) groups, 1352 cm À1 for CÀNb ending, and 1190 cm À1 for CÀOb ending.…”
mentioning
confidence: 95%
“…[9] The other is dehydrogenation of intermediates generated from the condensation of o-aminophenol/o-aminothiophenol/o-phenylenediamine with aldehydes. [10] For example, in 2014, Doo Ok Jang and his colleagues developed a convenient solvent-free method for the synthesis of benzothiazole, benzimidazole and benzoxazole derivatives using recyclable ZnO-NPs through ball-milling conditions (Scheme 1a). [11] This process provided environmentally friendly reaction conditions that were very efficient even on a gram scale and still allowed the products to easily be separated from one another.…”
Section: Introductionmentioning
confidence: 99%
“…During our previous study,9 we found that iodide could act as an efficient catalyst for the synthesis of benzimidazoles in dry solvents, and developed a novel protocol for the synthesis of benzimidazoles under anhydrous conditions via aerobic oxidative cyclization using iodide as a nucleophilic catalyst 9,13,14. Thus, we decided to explore the possibility of the formation of 3a‐MIDA from 1a with 2a‐MIDA using KI as a nucleophilic catalyst.…”
Section: Methodsmentioning
confidence: 99%